Detection of coumarin derivatives of Viola odorata cultivated in Iraq - Zainab Aziz Ali; Ibrahim Saleh; Widad M K Alani (Wolters Kluwer Medknow Publications, 2023)
Like other members of the viola family, Viola odorata may be found naturally occurring in Europe and Asia. This little plant is tough and perennially herbaceous. It's also known as sweet violet and English violet. There are several medicinal uses for this flowering plant, including its ability to fight cancer, bacteria, and inflammation., antioxidant activity, and antipyretic activity. The phytochemical studies of different parts of Viola odorata resulted in the isolation of different chemical constituents such as Coumarins, caffeic acid, methyl salicylate, flavonoids (Quercetin, kaempferol), glycosides (Rutin), and terpenoids (stigma sterol). Coumarins are important natural phenolic compounds of the family of benzopyrone. Coumarin's basic structure consists of a pyrone ring fused with a benzene ring. Umbelliferone and esculetin are the most common simple coumarins in nature. Coumarins become an attractive backbone drug with innovative impacts on illnesses and reduced side effects on healthy cells. Anti-inflammatory, anti-carcinogenic, and other biological properties are among those attributed to coumarins derivatives. In this study, Umbelliferone and esculetin of Viola odorata were identified by TLC, and HPTLC.